Respuesta :

Option B : [tex]y=-\frac{1}{2}[/tex] is the horizontal asymptote.

Explanation:

The function is [tex]y=\frac{-4 x^{6}+6 x+3}{8 x^{6}+9 x+3}[/tex]

The horizontal asymptote can be determined by

[tex]y=\frac{leading \ coefficient \ of \ numerator}{leading \ coefficient \ of \ denominator}[/tex]

Thus, from the function, the leading coefficient of numerator is -4

The leading coefficient of denominator is 8

Thus, substituting the values in the formula [tex]y=\frac{leading \ coefficient \ of \ numerator}{leading \ coefficient \ of \ denominator}[/tex] , we get,

[tex]y=\frac{-4}{8}[/tex]

Dividing, we get,

[tex]y=\frac{-1}{2}[/tex]

Thus, the horizontal asymptote is [tex]y=\frac{-1}{2}[/tex]

Hence, Option B is the correct answer.

ACCESS MORE